Constructivist Theories of Piaget and Vygotsky: General Teaching Implications - Kouicem, Khadidja; Kelkoul, Nachoua (University of Eloued جامعة الوادي, 2016)
There are many different learning theories that can be used to help guide a teaching/ learning process. Constructivism is one theory that explains how people might acquire knowledge and learn. The theory suggests that people construct their own understanding and knowledge of the world by testing ideas and approaches based on their prior knowledge and experience. Jean Piaget and Lev Vygotsky are two eminent figures in the cognitive development (development of constructivist theories). While there are similarities between the theories of Piaget and Vygotsky, differences exist, and those differences are critical to the understanding and application of the theories in educational settings and have great impact on the teaching methods. We can distinguish therefore between cognitive constructivism which is about how the individual learner understands things, in terms of developmental stages and learning styles, and the social constructivism, which focuses on how meaning and understanding grow out of social encounters.
THE SECOND NATIONAL CONFERENCE ON LANGUAGE, MIND AND LEARNER'S COGNITIVE CAPACITIES March, 7th/8th 2016 University of Eloued
Keywords: Constructivism, Cognitive Constructivism, Social Constructivism, Teaching Implications